Conjugated polymers containing diketopyrrolopyrrole units in the main chain - Tieke, Bernd (Beilstein-Institut, 2010)
Research activities in the field of diketopyrrolopyrrole (DPP)-based polymers are reviewed. Synthetic pathways to monomers and polymers, and the characteristic properties of the polymers are described. Potential applications in the field of organic electronic materials such as light emitting diodes, organic solar cells and organic field effect transistors are discussed.